PWE-049 Assessment of symptomatic hypophosphatemia with iron isomaltoside in inflammatory bowel disease patients. (8th June 2018) - Reinisch, Walter; Dahlerup, Jens Frederik; Derman, Richard
Abstract : Introduction: Patients with inflammatory bowel disease (IBD) often need intravenous (IV) iron but some IV irons have been associated with hypophosphatemia in as many as 47%–70% of patients with iron deficiency anaemia (IDA) without chronic kidney disease with severe hypophosphatemia seen in up to 13% of the patients. Hypophosphatemia has been linked to acute symptoms such as pain, nausea and muscle weakness, and more long term complications such as development of osteomalacia with bone pain, fractures and pseudo fractures. Transient hypophosphatemia may occur in response to rapid cellular proliferation due to transcellular shift of phosphate from the extracellular fluid into cells whereas longer lasting hypophosphatemia described after treatment with some IV irons seems related to renal phosphate wasting mediated through an increase in the phosphaturic hormone fibroblast growth factor (FGF23). This analysis was done to investigate whether phosphate levels needs to be considered during treatment with iron isomaltoside. Methods: The data presented here is from a pooled analysis of IBD patients from 3 clinical trials of iron isomaltoside performed in IBD patients with IDA. Outcome measures were s- phosphate and adverse drug reactions linked to low levels of serum phosphate. Intact FGF23 (iFGF23) was measured in a subgroup of patients. Results: 255 patients (89 men, 166 women) were included in the analysis. Cumulative doses of ≤1000 mg or >1000 mg iron isomaltoside were administered in 189 and 66 patients, respectively. Hypophosphatemia ( s -phosphate <2 mg/dL) was observed in 7.9% and 6.1% in patients dosed with ≤1000 mg and >1000 mg iron isomaltoside, respectively (p = 0.8) and 7.4% for the total population. The drop in phosphate was typically just below 2 mg/dL, appeared one week after the iron infusion and was normalised two weeks after the infusion. These events were asymptomatic, not reported as adverse events, and assessed as non-clinically significant. No severe hypophosphatemia ( s -phosphate <1 mg/dL) was observed. No increase in iFGF23 was seen throughout the study in the subgroup of patients (n=21) where it was measured. Conclusions: No severe hypophosphatemia was observed in IBD patients treated with iron isomaltoside and the small dip in s-phosphate observed among 7.4% of the patients was independent of dose. Signs of iFGF23-induced renal phosphate wasting were not observed in the sub-population of patients examined.